The Condition of Megabenthos in the Coral Reef Ecosystem on Salawati-Batanta Island, West Papua - Hendrik A. W. Cappenberg; U. Y. Arbi; J. Souhoka; N. W. P. Sari; E. Widyastuti; Susetiono; F. D. Hukom; T. Sidabutar (Advanced Research in Biological Science Vol. 1, 2023)
This study investigates the status of the megabenthos population in the coral reef ecosystem of Salawati-Batanta Island in West Papua. Salawati-Batanta Island is known for its extensive coral reefs and rich variety of megabenthos, including polychaetes, crustaceans, echinoderms and mollusks. The study examines the abundance, diversity, and distribution of megabenthos species in this region. Data on megabenthos was collected from transects conducted along the coast at depths of 3 to 7 meters. Observations were conducted between 2015 and 2019, with additional data collected in 2021 to ensure a comprehensive analysis. The results consistently showed a stable diversity of eight megabenthos species, which could be classified into different ecological groups based on their importance. These groups include indicator species, coralivorous species, and economically valuable species. It has been found that the distribution of certain species, such as L. laevigata and Tridacna spp. is widespread throughout the study area, indicating a healthy population. Species like Panulirus sp. and A. planci showed a more restricted distribution. The study also found that coral-eating groups were low in number and posed no significant threat to the coral colonies. The density of L. laevigata and Tridacna spp. remained relatively stable throughout the observation period, while Holothuria spp. showed a declining trend, particularly in commercially valuable species, suggesting possible overexploitation. Overall, the study suggests that the megabenthos community in the coral reef ecosystem of Salawati-Batanta Island is currently in good condition. However, it emphasizes the importance of implementing effective conservation measures to ensure the long-term sustainability of these coral reefs and prevent over-exploitation of economically valuable species.